Kajian Yuridis Pelanggaran Syarat Calon Kepala Daerah Dalam Undang - Undang Nomor 10 Tahun 2016 Terhadap Penggunaan Status Kewarganegaraan Ganda - Muzayanah, Muzayanah; Listyarini, Dyah; Sukarman, Sukarman (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
The election of regional heads is an activity in the context of implementing a democratic government system and aims to obtain quality regional leaders, able to work honestly, cleanly and with dignity. Among the requirements for a regional head candidate, which is regulated in Law Number 10 of 2016 concerning Regional Head Elections, those who register as regional head candidates are Indonesian citizens (WNI). Considering the principle of citizenship that applies in the Republic of Indonesia based on Law Number 12 of 2006 concerning Citizenship is Monopatride, every citizen of the Republic of Indonesia only has single citizenship status, except for children born after the enactment of the Citizenship Law can have dual citizenship. This study examines the dual citizenship status of the candidate for Sabu Raijua regent who, at the time of registering to participate in the election of a regional head candidate, it turns out that the Sabu Raijua regent does not renounce his American citizenship status, so he remains dual citizenship. This research has a normative juridical specification. Research method with library research (library research). The data collection method uses secondary data in the form of primary legal materials and secondary and tertiary legal materials. The results of the study on violations of the requirements for regional head candidates in regional head elections based on Law number: 10 of 2016 concerning Regional Head Elections against the use of dual citizenship status. Violations committed by the regent of Sabu Raijua against the requirement to register as a candidate for regional head must be a citizen of the Republic of Indonesia, but this was not fulfilled by the person concerned.